The Effects of Cooperative Project-Based Learning through Social Praxis Project Proposal Development on Students’ Conceptual Understanding and Concept Application - Yuliati Yuliati; Punaji Setyosari; Dedi Kuswandi; Made Duananda Kartika Degeng; Moch. Nurfahrul Lukmanul Khakim (FKIP Universitas Lampung, 2026)
This study aims to determine the effectiveness of the Cooperative Project-Based Learning (CPjBL) strategy on students’ conceptual understanding and concept application abilities compared to the Project-Based Learning (PjBL) strategy, as well as to analyze the influence of Field Independent (FI) and Field Dependent (FD) cognitive styles on student learning outcomes. The study employed a quantitative approach using a quasi-experimental research design with a non-equivalent control group factorial design of 2 × 2. The research subjects consisted of 100 students from the History Education Study Program at Universitas Negeri Malang who were divided into experimental and control groups. Data collection was conducted through conceptual understanding tests, concept application tests, and the GEFT (Group Embedded Figures Test) cognitive style instrument. Data were analyzed using MANOVA after fulfilling prerequisite tests, including normality, homogeneity, linearity, and multicollinearity tests. The findings indicate that learning strategies significantly affect students’ conceptual understanding and concept application abilities. Students who learned using the CPjBL strategy achieved higher average learning outcomes compared to those who learned using the PjBL strategy. In conceptual understanding ability, the CPjBL group obtained an average score of 84.42, while the PjBL group achieved an average score of 79.30. In concept application ability, the CPjBL group obtained an average score of 90.02, whereas the PjBL group achieved an average score of 86.14. The results also revealed that FI and FD cognitive styles did not have a significant effect on students’ conceptual understanding or concept application abilities. In addition, an interaction effect between learning strategies and cognitive styles on student learning outcomes was identified. The findings confirm that the CPjBL strategy is more effective in improving conceptual understanding and concept application abilities because it creates an active, collaborative, and student-centered learning environment. This strategy also provides opportunities for students to develop critical thinking, collaboration, communication, and problem-solving skills throughout the learning process. Keywords: cooperative project-based learning, project-based learning, cognitive style, conceptual understanding, concept applications.